Challenging the right to collective welfare: A legal and human rights review of modern cooperative capitalization in Indonesia - Silvia Anas (PT WIM Solusi Prima, 2026)
The establishment of Village/Sub-District Red and White Cooperatives (Koperasi Desa/Kelurahan Merah Putih or KDKMP) represents one of the Indonesian government's strategic initiatives to strengthen the people’s economy through the development of cooperative institutions at the village and sub-district levels. This policy is expected to enhance community economic capacity, expand business opportunities, and strengthen national supply chains. Nevertheless, the institutional strengthening of cooperatives through various regulatory instruments has generated debate regarding the balance between governance professionalization and the preservation of economic democracy as the fundamental character of cooperatives. This article aims to analyze the juridical implications of cooperative formalization and capitalization policies on the principles of economic democracy and the protection of the right to collective welfare within the Indonesian legal system. The study employs a normative legal research method using statutory, conceptual, and human rights approaches. The legal materials consist of legislation, international human rights instruments, legal doctrines, and relevant academic literature. The analysis focuses on Minister of Finance Regulation Number 49 of 2025, Presidential Instruction Number 9 of 2025, and Presidential Instruction Number 17 of 2025 as the principal regulatory framework governing KDKMP. The findings indicate that the formalization and strengthening of cooperative governance are intended to improve institutional effectiveness and organizational accountability. However, increasing administrative and managerial standardization may affect the cooperative’s character as an institution founded upon solidarity, member participation, and mutual cooperation. This article proposes a conceptual construction of the right to collective welfare as an analytical framework for assessing the compatibility of state economic policies with the principles of economic democracy, welfare state objectives, and the protection of economic and social rights.